Prototype Smart Parking Berbasis IoT - Istiqlal, Alamullah; Zaen, Mohammad Taufan Asri Zaen; Pratama, Walidi Wahyu (Jurnal Teknik Informatika dan Elektro, 2023)
As the STMIK Lombok academic community increases every year, vehicle users at STMIK Lombok also increase. This encourages the need for parking in the STMIK Lombok area which must be managed properly. Currently, the academic community sometimes has to go around to find an available parking space, as a result, parking users park their vehicles in random places so that they look untidy and disorderly. The parking area and system on the STMIK Lombok campus still uses a manual system, namely with a security guard and monitoring system, vehicles entering and leaving are not recorded and checked. Based on the existing problems, this study initiated parking management on the STMIK Lombok campus with a smart system (Smart Parking). This study used the R&D method with site observation, problem analysis, making prototypes and trials. This design is based on the Internet of Things (IoT) which is connected to the user's smartphone, with the main components being the NodeMCU ESP8266, Arduino UNO, IR Obstacle Sensor, and RFID Reader. This research is expected to provide solutions to parking problems at STMIK Lombok with a smart system that sends information on the availability of empty slots to user devices, an automatic portal system, the number and identity of vehicles is recorded so that parking management will be more effective and efficient.